Comparative study of GC‐MS characterization, antioxidant activity and hyaluronidase inhibition of different species of Lavandula and Thymus essential oils. (11th September 2015) - Carrasco, Alejandro; Tomas, Virginia; Tudela, Jose; Miguel, Maria G.
Abstract: The chemical compositions of essential oils of Lavandula angustifolia, Lavandula latifolia, Lavandula hybrida cultivar Grosso and cultivar Super, Thymus zygis with high proportions of thymol and linalool and Thymus hyemalis, from Murcia country (Spain), were studied in relative (%), absolute (mM) and chiral concentrations by GC/MS. Hyaluronidase inhibition and antioxidant activities of the essential oils were evaluated using ABTS +, DPPH, ORAC, chelating power, hydroxyl radical, nitric oxide, TBARS and reducing power assays. Linalool and linalyl acetate were the most abundant components in the Lavandula genus whereas thymol, linalool and 1, 8‐cineole were the most abundant molecules in the respective Thymus species. Chiral determination of the main components showed (+)‐enantiomers like terpinen‐4‐ol, β‐pinene, borneol and α‐terpineol and (−)‐enantiomers like linalool, linalyl acetate and camphene in Lavandula sp. In the case of Thymus sp. (+)‐enantiomers like α‐pinene, limonene, terpinen‐4‐ol and α‐terpineol and (−)‐enantiomers like borneol were found. Essential oils containing thymol were found especially powerful in all assays but chelating power, ORAC and hydroxyl radical scavenging assays. The capacity for inhibiting hyaluronidase showed that T . zygis with a high proportion of thymol was the most effective inhibitor. Essential oils containing thymol and linalool/linalyl acetate have a potential use as antioxidant agents. Thymol shows strong inhibition of hyaluronidase. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Aromatic and chiral compositions of L. angustifolia, L. latifolia, L. hybrida cultivar Grosso and cultivar Super, Thymus zygis with high proportion of thymol and linalool and Thymus hyemalis essential oils were determined. Antioxidant and hyaluronidase inhibitory activities were evaluated and correlated with the essential oil composition.